THU0624-HPR COMPARISON OF WRIST PROPRIOCEPTION, GRIP STRENGTH AND PINCH STRENGTH IN PATIENTS WITH PSORIATIC ARTHRITIS AND RHEUMATOID ARTHRITIS: PRELIMINARY STUDY. (2nd June 2020) - Köprülüoğlu, M.; Naz Gürşan, İ. and Solmaz, D. and Otman, E. and Durak Ediboglu, E. and Akar, S.
Abstract : Background: Hand articular damage occurs in rheumatoid arthritis (RA) and functional ability deteriorates as the disease progresses. Limitation of hand motion, oedema, pain etc. factors contribute to reduce grip strength, pinch strength and joint position sense; this problems contribute to function and disability. Following RA, affecting grip and pinch strength (1) and joint position sense (2) was reported former research. But there is a little knowledge about disabilitiy of hand functions in psoriatic arthritis (PsA). Objectives: To compare joint position sense, grip strength and pinch strength in patient with PsA and RA. Methods: In our cross sectional study, 23 RA patients [Mean age; 52.7±12.6, Women:20(87.0%)] who were classified according to the ACR 2010 criteria and 19 PsA patients [Mean age 53.5±12.6, Women:14 (%73.7)] who were classified according to the CASPAR criteria were included.It was recorded demographic and clinical data of patients. Wrist position sense was evaluated by goniometric re-position error test (in 30◦ wrist extansion, 3 repeat). Grip strenght was examined using a hand dynamometer (Lafayette Proffessional Hand Dynamometer, USA) and pinch strength (two point, three point, lateral) was evaluated by pinchmeter (Lafayette, USA). Results: Patients were similar in terms of age, gender, disease duration, morning stiffness duration, pain of hand joints, number of tender and swallen joints and disease activity (p>0.05). RA patients had longer disease duration (p=0.004) and lower ESR levels (p=0.046) compared to PsA. Grip and pinch strength were found similar in both dominant and non-dominant side between RA and PsA patients (Table 1 ). Wrist joint position error was higher in PsA group in non-dominant side (p=0.011). Conclusion: Our study showed that patients with PsA had hand impairment as much as RA patients. We think, hand assessment in patients with PsA rehabilitation programme is essential for clinicians. There is need future studies including asymptomatic healthy group to interpret of results in detailed. References: [1]VLIET, TP Vlieland, et al. Determinants of hand function in patients with rheumatoid arthritis. The Journal of rheumatology, 1996, 23.5: 835-840. [2]FERRELL, W. R.; CRIGHTON, A.; STURROCK, R. D. Position sense at the proximal interphalangeal joint is distorted in patients with rheumatoid arthritis of finger joints. Experimental Physiology: Translation and Integration, 1992, 77.5: 675-680. Disclosure of Interests: None declared